EMPIRICAL EVIDENCE OF THE SUITABILITY OF IFRS FOR BANKING SECTOR IN SUB-SAHARAN AFRICAN COUNTRIES - Tiruneh, Dawit Tadesse (Copernican Journal of Finance & Accounting, 2021)
The reason for this investigation was to survey the appropriateness of International Financial Reporting Standards (IFRS) in sub-Saharan African nations banking sector like Ethiopia. The following research endeavors to acquire experiences into the benefits and detriments of IFRS execution in Ethiopian Banking sector depending on the view of banks financial directors, scholastics in accounting and external auditor. Examination is insightful of online overview, which intends to clarify the appropriateness of IFRS as opposed to depict a population. Along these lines, representativeness of the example to the population was not the objective of the examination; it endeavors rather to guarantee legitimacy of the information by applying purposive testing (Oppenheim, 1992). In such manner an aggregate of 30 surveys were conveyed to banks financial supervisors, scholastics and external auditors who have rich information and involvement with IFRS execution in financial sector in Ethiopia. Of the 26 answers (87 percent), 26 finished polls were broke down. The outcomes recommend that IFRS execution is appropriate for the banking sector of Ethiopia regardless of whether banks are causing extra significant expenses to carry out the standards. The selection of IFRS gives numerous benefits to the financial sector climate without logical inconsistency with Ethiopian financial laws and corporate duty. The advantages that the financial sector in Ethiopia will get from IFRS execution pertinently and dependably addresses the financial reports more than its execution cost.